Impact of celebrity endorsement on attitudes toward voluntary blood donation - HOUNKPEDJI, Koffi (Archives of Business Research, 2022)
The use of celebrities to promote voluntary blood donation is a recurrent practice but no study to our knowledge has addressed the subject. This study showed that he persuasives characteristics of celebrities commonly considered in the commercial field are not all adapted to the social context. Indeed, in the context of solicitation of voluntary blood donation, the study showed that the reliability and notoriety of the celebrity in addition to the feelings of the audience toward him must be the determining attributes. In addition, the results revealed that the reliability and notoriety of the celebrity are the factors that favorably influence the attitude towards voluntary blood donation.